Peningkatan Pemahaman Pasien Dan Keluarga Pasien Tentang Tindakan Paska Pemeriksaan Colon In Loop Melalui Gerakan Ayo Konsumsi Serat Dan Air Putih (Akon Sapu) - Hidayati, Alpha Olivia; Sarereake, Cindy E; Sri Lestari, Indah Dewi; Making, Silfiana Sura; Herani, Yoseph Aloysius (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Colon in Loop Radiological Examination is a radiological examination of the large intestine (colon) to see abnormalities in the area using contrast media. The contrast medium used is Barium Sulfate BaSO4. The characteristics of Barium Sulfate easily settles, so it needs an action to clean the remaining barium in the colon after examination so that it does not cause intestinal obstruction. One of the efforts to increase the understanding of the patients and the patient’s familiy with the activities of “AKON SAPU” (Let’s consume fiber and water) movement after Colon in Loop Examination. The method of implementing the activity is using a two-way interactive method, namely 1). Giving questionnaires to patients and their families as many as 23 people who will do a Colon in Loop Examination at RSPAU dr. S. Hardjolukito; 2). Socialization to patients and their families with the help of leaflets; 3). Giving questionnaires to patients and their families. The results obtained indicate that the patient and the patient’s familiy were enthusiastic abaout this activity as evidenced by the many questions asked. There was a 35% increase in understanding of the post-Colon in Loop Examination. So it can be concluded that the “AKON SAPU” (Let’s consume fiber and water) movement after Colon in Loop examination can increase understanding of the patient and the patient’s familiy.